Case report: Primary cardiac undifferentiated sarcoma complicated by esophagus stenosis - Yuxin Ge; Xiaopan Lv; Rui Zhang; Dongxiao Hao; Guifei Si; Yuquan Li; Xuemin Yuan; Xiuping Li (Frontiers in Oncology)
In this study, we present the case of a 38-year-old woman who was diagnosed with primary cardiac undifferentiated sarcoma after hospital admission. Following postoperative treatment that included radiotherapy and immunotherapy, the patient developed esophagus stenosis.